From physiological adaptations to endurance performance: it is time to bridge the gap - Brocherie, F.; Goto, K.; Dupuy, O.; Gruet, M.; Vercruyssen, F.; Louis, J. (Frontiers in Sports and Active Living, 2021)
Editorial on the Research Topic From Physiological Adaptations to Endurance Performance: It Is Time to Bridge the Gap